-9x-3=60

Simple and best practice solution for -9x-3=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9x-3=60 equation:


Simplifying
-9x + -3 = 60

Reorder the terms:
-3 + -9x = 60

Solving
-3 + -9x = 60

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -9x = 60 + 3

Combine like terms: -3 + 3 = 0
0 + -9x = 60 + 3
-9x = 60 + 3

Combine like terms: 60 + 3 = 63
-9x = 63

Divide each side by '-9'.
x = -7

Simplifying
x = -7

See similar equations:

| 27-4m=3 | | 6(2x+1)+2=2(4x+1)+2(2x+3) | | 9z-8z=5z+7+3z | | 0=16t^2+8+15 | | 40=(2x-1) | | 10x+5y=95 | | 9C=5F-160 | | -7a-10a= | | 4x+2=7x+7 | | -2x^2+10x-1=0 | | 3=z+6 | | 125w^6+27g^3=0 | | 3x^4-15x^2-72=0 | | 18x^2+15x=0 | | -20+7z+6z^2=0 | | 7x+15= | | 2x^2-7x=-6 | | 6t^2-96=0 | | 18x^2+21x=0 | | 7+2t+3t= | | -6wx^5(3w^6+4w^3x^4-9x^4)= | | 4a+12=3a+32 | | 13-2x=x^2-25 | | x^2+21=5 | | 7-2k=15 | | 6.7+12m-9.3=6.4 | | x^2+2=66 | | X+(x*1.25)=360000 | | 4x^2-36x+9=0 | | 0.1r+0.05x-300=105 | | x=1.5y | | 0.05y+0.03y(y+50)=17.5 |

Equations solver categories